1967
DOI: 10.2134/agronj1967.00021962005900030018x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Population and Row Spacing on Evapotranspiration and Water‐Use Efficiency by Soybeans1

Abstract: During 1964 and 1965, Chippewa and Merit soybeans were planted in 20‐, 61‐, and 102‐cm rows at populations attained from seeding rates of approximately 34, 67, and 135 kg/ha. Evapotranspiration from planting to the first killing frost ranged from 32.8 to 38.0 cm and from 42.3 to 46.2 cm for 1964 and 1965, respectively. Neither row spacing nor plant population significantly affected evapotranspiration during the 2 years studied. Generally, highest water‐use efficiencies were obtained for the lower plant populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Although these effects of row spacing on soybean yield appear to be contrary to some previously published results (3,6,8,9,10,17), the explanation given above fits the results of the experiments reported by Taylor (16). In years of high rainfall in Iowa, he obtained increased soybean yield from narrow rows, but found no effect of row spacing in years of belownormal precipitation.…”
Section: Soybean Yieldssupporting
confidence: 63%
See 1 more Smart Citation
“…Although these effects of row spacing on soybean yield appear to be contrary to some previously published results (3,6,8,9,10,17), the explanation given above fits the results of the experiments reported by Taylor (16). In years of high rainfall in Iowa, he obtained increased soybean yield from narrow rows, but found no effect of row spacing in years of belownormal precipitation.…”
Section: Soybean Yieldssupporting
confidence: 63%
“…Timmons et al (17) found that greatest soybean yields were obtained with low plant population when planted in narrow rows, but higher planting rates were required for maximum yield in wider rows. Cooper (3) found similar trends at some Illinois locations, but not at others.…”
mentioning
confidence: 99%
“…Realization of the potential benefits of narrow-row spacings depends upon the adequacy of moisture during the growing season. Narrow rows usually improve water use efficiency when adequate moisture is available (16,21 ). When moisture is severely limiting, this factor rather than efficiency of light interception apparently establi:;hes the yield potential of the crop (20).…”
mentioning
confidence: 99%
“…Timmons et al (1967) found that evapotranspiration differences between row spacings and populations were small and water use efficiency values for each year in the study were within a relatively narrow range. Higher water use efficiencies were obtained for low plant population in narrow rows.…”
Section: Introductionmentioning
confidence: 70%